Performance of the nitrogen removal, bioactivity and microbial community responded to elevated norfloxacin antibiotic in an Anammox biofilm system - Zhang, Xiaojing; Chen, Tao; Zhang, Jun; Zhang, Han; Zheng, Shuhua; Chen, Zhao; Ma, Yongpeng (Chemosphere (Oxford), 2018)
Antibiotic pollution in nitrogen contained wastewater is an urgent issue. In this study, the nitrogen removal, biofilm property and microbial community of Anammox system were investigated with elevated norfloxacin (NOR) feeding. Batch experiments were carried out to detect the specific anammox activity (SAA) in each phase. Anammox system could resist NOR in 0.001–50 mg L−1, in which the nitrogen removal was firstly limited to 0.220 from the initial 0.345 by NOR suppression and then regained to 0.354 kg m−3 d−1 after acclimatization. SAA decreased to 7.56 from the initial 10.84 and then climbed up to 11.01 mg g−1 SS, while the relative abundance of Candidatus Kuenenia decreased to 11.33% and then picked up to 25.28% from the initial 20.74%. The suppression threshold on Anammox was calculated as 50–100 mg L−1 NOR, the NRR, SAA and Candidatus Kuenenia abundance all recovered to almost the initial level when NOR feeding was terminated. •The nitrogen removal of Anammox could resist the NOR antibiotic in 0.001–50 mg L−1.•The irreversible suppression threshold of NOR on Anammox was 50–100 mg L−1.•Beta-proteobacteria had a pronouncing share increase under high NOR load.•Long-term exposure in NOR stimulated the growth of Candidatus_Kuenenia after acclimatization.•Anammox biofilm recovered to almost the initial level when NOR feeding was terminated.